Non-financial reporting in non-profit organisations: the case of risk and governance disclosures in UK higher education institutions - Mohamed Elmagrhi (Accounting Forum, 2023)
This paper investigates non-financial reporting in non-profit organisations. Specifically, it examines the extent to which UK higher education institutions (HEIs) make voluntary disclosures relating to risk management practices, and investigates whether composite governance quality index and senior management team characteristics can influence such risk disclosures. Using a sample of UK HEIs over a number of years and drawing insights from neo-institutional theory, our findings are three-fold. First, our baseline findings contribute to the literature by showing that the level of risk disclosure among HEIs in the UK is relatively low, especially when compared to the findings of prior studies that have been conducted on similar-sized publicly traded corporations. Second, we contribute to the literature by providing timely evidence on the impact of governance quality on risk disclosure. In particular, our evidence contributes to the existing literature by demonstrating that better-governed HEIs tend to engage in higher risk disclosures than their poorly-governed counterparts. Finally, our study contributes to the extant literature by providing new evidence that offers support for the “shared” governance model among UK HEIs. Specifically, our findings show that the positive governance quality–risk disclosure relationship is moderated/explained largely by the characteristics of the senior management team. Our findings are robust to controlling for endogeneities and alternative estimation techniques, with major implications for non-financial reporting.